TINJAUAN LITERATUR SISTEMATIS: PENGARUH HYPERMEDIA TERHADAP HASIL BELAJAR SISWA (2015-2025) - Afandi, Mohammad Iqbal; Tri Atmaja, Hamdan; Ellianawati , Ellianawati; Avrilianda, Decky (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to examine the effect of using hypermedia on student learning outcomes in the 2015-2025 timeframe. The background of this study is the low student learning outcomes due to the use of conventional learning methods with minimal media variations. This study was conducted through a systematic literature review using the PRISMA approach, which includes a process of identification, screening, eligibility and inclusion from five scientific databases. Of the 81 articles reviewed, 10 were selected as the main focus of analysis. The results showed that the use of hypermedia can significantly improve student learning outcomes, both cognitively and affectively. Hypermedia is effective in supporting diverse learning styles, simplifying complex material, and increasing student engagement and motivation. It also acts as an instructional and evaluative instrument in both online and offline learning. However, the effectiveness of hypermedia is highly dependent on teacher readiness, media design and infrastructure availability. The conclusion of this study confirms that hypermedia is a potential pedagogical tool to improve student learning outcomes, the quality of active, contextual and student-centered learning, and has great potential in the transformation of 21st century education.